Ancient Christian writers ; v. 26 the works of the fathers in translation - Quasten, Johannes; Plumpe, Joseph C.; Lawson, R.P. (Westminster, MA Newman, 1957)
Contents : "The Song of Songs : commentary and homilies" by Origen ; translated and annotated by R.P. Lawson. Includes bibliographical references and index.
Keywords: Bible. O.T. Song of Solomon -- commentaries; Church history -- early and primitive, ca 30-600 -- sources